Racket holding forces for playing a forehand stroke at varied swing speeds in table tennis - Watanabe, K.; Kinoshita, H.; Ishido, W.; Hashiguchi, T. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to investigate racket gripping forces in table tennis when 9 experienced players struck a ball at different swing speeds with a forehand stroke. Handle grip force, and paddle pressing forces by the index finger and thumb, and racket swing speed were measured using a sensor racket developed, and a motion capture system. The handle grip force exhibited peaks before and after the ball impact. The peak handle forces increased with swing speed non-linearly. In the fast drive stroke, the pre-impact peak of the grip force summed for the handle and fingers reached on average of 85 N with a range of 30 N to 135 N. This large individual variability was considered a reflection of differences in racket handling skills acquired in long-term training under different coaches.